Opportunities and Prospects of Cassava Feeding in Swine: A review - Barman, Keshab; Konwar, Dipanjali; Banik, Santanu; Rajkhowa, Swaraj (Indian Journal of Animal Nutrition, 2018)
Cassava tubers are rich in carbohydrate and can be successfully used as an energy source for swine. cassava could be used in pig rations balanced for nutrients especially protein/limiting amino acids at levels of50-70% in diets for growing finishing pig without adversely affecting production performance as well as carcass characteristics. Cassava tubers could be a cheaper energy source for swine feeding. The economic importance of cassava, its production and the technical aspects of the limitations are also discussed. The opportunities and prospects of cassava feeding in pig are briefly reviewed in this paper.